A Comprehensive Review of Kojic Acid Dipalmitate: Advanced Skin Brightening Technology in Contemporary Cosmetics - Prameswari, Alifia Ramadhanty; Chaerunnisaa, Anis Yohana; Husni, Patihul (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2025)
Introduction: Hyperpigmentation disorders represent a significant concern in dermatology and cosmetic science, with traditional treatments often limited by stability issues, irritation potential, and suboptimal efficacy. Kojic Acid Dipalmitate (KAD), a lipophilic derivative of kojic acid, has emerged as a promising alternative in advanced skin brightening formulations due to its enhanced physicochemical properties and improved safety profile. Aims: This review aimed to evaluate the stability considerations, optimal concentration ranges, delivery system technologies, and clinical efficacy of KAD in topical applications for hyperpigmentation management. Methods: A comprehensive analysis of recent literature was conducted, examining in vitro studies assessing tyrosinase inhibition and stability profiles, ex vivo investigations of skin penetration and retention, and in vivo clinical evaluations of efficacy and safety. Particular attention was directed toward advanced delivery systems including solid lipid nanoparticles, nanoemulsions, and ethosomal formulations. Results: KAD demonstrates superior stability against oxidation, pH fluctuations, and thermal stress compared to conventional kojic acid. Optimal formulations contain 1-5% KAD, with sophisticated delivery systems achieving comparable efficacy at lower concentrations (0.1-0.2%) due to enhanced bioavailability. Solid lipid nanoparticles (70 nm) exhibited controlled release kinetics with 80% KAD released over 24 hours, while nanoemulsions (<130 nm) showed >95% stability for 30 days under refrigeration. Clinical evaluations confirmed 40-50% reduction in melanin indices with minimal irritation, along with improved skin hydration and elasticity. KAD also demonstrated antimicrobial activity against Staphylococcus aureus and antioxidant capacity comparable to 1 mM ascorbic acid. Conclusion: KAD represents a significant advancement in depigmentation technology, successfully balancing efficacy and tolerability through enhanced stability and targeted delivery. Its integration into sophisticated vehicle systems optimizes performance while minimizing adverse effects, positioning KAD as an exemplary ingredient for next-generation skin brightening formulations in contemporary cosmeceuticals.